2018
DOI: 10.1002/ep.13094
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of households’ willingness to accept the ecological restoration of rivers flowing in china

Abstract: During the past decade, many urban rivers in China have undergone ecological restoration overseen by government agencies at the local and national level. Ecological restoration efforts such as this can improve the welfare of urban residents. This study reports the willingness to accept (WTA) for Pingjiang and Guangtaiwei rivers degradation in Suzhou based on a contingent valuation study of 426 respondents. Our results indicate that 48% of respondents would not accept any money as compensation for river degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Increased environmental control has been demonstrated to be detrimental to economic expansion [4]. Compared to the lack of flexibility and the long-term incentive effect of mandatory administrative control, market-based environmental regulation policies use economic resource allocation to realize emission control and emission reduction of polluting enterprises and assign economic value to abatement behaviors [5], which is a more endogenous incentive [6]. As a typical market-based environmental policy, a carbon ETS makes enterprises trade emission quotas in the carbon market by granting carbon emission rights quotas.…”
Section: Introductionmentioning
confidence: 99%
“…Increased environmental control has been demonstrated to be detrimental to economic expansion [4]. Compared to the lack of flexibility and the long-term incentive effect of mandatory administrative control, market-based environmental regulation policies use economic resource allocation to realize emission control and emission reduction of polluting enterprises and assign economic value to abatement behaviors [5], which is a more endogenous incentive [6]. As a typical market-based environmental policy, a carbon ETS makes enterprises trade emission quotas in the carbon market by granting carbon emission rights quotas.…”
Section: Introductionmentioning
confidence: 99%
“…This condition was also perceived in the study's findings wherein more respondents from small household sizes tend to be more willing to pay for the bid prices (Table 7). This trend is also evident in the studies of Moffat et al (2011), Zelalem andBeyene (2012), andYifei et al (2018), wherein they observed that as family size increases, the household tends to have a negative attitude toward willingness to pay.…”
Section: Determination Of Willingness To Pay and Factors Influencing Itmentioning
confidence: 52%